Soil Transmitted Helmint on Lettuce (Lactuca sativa L.) From Plantation and Post-Irradiation - Narti Fitriana; Nelly Suryani; Yani Indriyani; Priyanti Priyanti (Al-Kauniyah: Jurnal Biologi, 2022)
AbstractSoil-Transmitted Helminth (STH) is a group of intestinal parasitic nematode worms that can infect humans. One of the transmissions to humans is consuming lettuce grown on soil media. This study aims to identify the types of intestinal parasitic nematodes found in lettuce and soil from plantations based in the Regency of Bogor, Cianjur, and Bandung and analyze the prevalence, intensity, and dominance categories before and after irradiation. The irradiation dose used was 5 kGy with a gamma irradiation source [60Co]. The descriptive method used in this study where the samples were collected from 9 sampling points at each study site. Identification showed that there were 3 types of intestinal parasitic nematodes found in lettuce, namely Ascaris lumbricoides (1,833 eggs), Strongyloides stercoralis (2 larvae), and Trichuris trichiura (91 eggs). The highest prevalence was found in A. lumbricoides (100%) which is classified %) classified as very severe contamination, very severe, and superinfection intensity of contamination criteria. The highest dominance of intestinal parasitic nematodes was found in A. lumbricoides. In the post-irradiated lettuce and soil samples was found eggs of A. lumbricoides and T. trichiura. The eggs of A. lumbricoides were the most common, 321 eggs were found in the post-irradiated lettuce, while 11 eggs of T. trichiura were found therein. Irradiation techniques can be used for the application of free-STH lettuce in the future, however, maintaining fresh food sanitation shall always be a priority preventive effort.AbstrakSoil Transmitted Helminth (STH) merupakan kelompok cacing nematoda parasit intestinalis yang dapat menginfeksi manusia. Salah satu transmisi kepada manusia adalah mengonsumsi selada yang ditanam pada media tanah. Penelitian ini bertujuan untuk mengidentifikasi jenis cacing nematoda parasit intestinalis yang ditemukan pada selada dan tanah asal perkebunan di Kabupaten Bogor, Kabupaten Cianjur, dan Kabupaten Bandung serta menganalisis kategori prevalensi, intensitas, dan dominansinya sebelum dan pascairadiasi. Dosis iradiasi yang digunakan adalah 5 kGy dengan sumber iradiasi gamma [60Co].  Metode deskriptif digunakan pada penelitian ini, sampel dikoleksi dari 9 titik sampling pada setiap lokasi. Identifikasi menunjukkan terdapat 3 jenis cacing nematoda parasit intestinalis yang ditemukan pada selada yaitu Ascaris lumbricoides (1.833 telur), Strongyloides stercoralis (2 larva), dan Trichuris trichiura (91 telur). Prevalensi tertinggi ditemukan pada A. lumbricoides (100%) tergolong tingkat kontaminasi kategori selalu dengan kriteria kontaminasi sangat parah, intensitas kontaminasi kategori super infeksi. Dominansi cacing nematoda parasit intestinalis tertinggi ditemukan pada A. lumbricoides. Pada selada dan sampel tanah pasca iradiasi ditemukan telur A. lumbricoides dan T. trichiura. Telur A. lumbricoides merupakan yang terbanyak, pada selada pasca iradiasi ditemukan 321 sedangkan T. trichiura ditemukan 11. Teknik iradiasi dapat digunakan untuk aplikasi selada bersih dari STH di masa datang namun menjaga sanitasi pangan segar merupakan usaha preventif prioritas.